Adjusting Productivity for Pollution in Selected Asian Economies - Dang, Thai-Thanh (OECD Green Growth Papers, 2014)
Multifactor productivity (MFP) is increasingly used in economic policy, not least to compute potential output. Most measures are based on a standard production function combining labour and capital, but do not incorporate the negative by-products of the production process such as air pollution that could have deleterious effect on health and productivity in the medium to long term (see for instance OECD (2014)). The failure to account for the costs of environmental damages and the benefits associated with emission reduction impart a bias to standard measures of MFP. Ignoring these dimensions can give a misleading idea of growth prospects over the medium to long term...